Armenian issue and truths : spring session of NATO Parliamentary Assembly, May 26-30, 2006, Paris = Question Armenienne et les verites : session de printemps de l’Assemblée Parlementaire de l’OTAN, 26-30 Mai 2006, Paris = Armenierfrage und Wirklichkeiten : Frühlingszusammensetzung von Parlamentarienversammlung von NATO, 26-30 Mai 2006, Paris = Ermeni meselesi ve doğrular : NATO Parlamenterler Asamblesi bahar toplantısı, 26-30 Mayıs 2006, Paris. - Akgül, Aziz. (Ankara)
35, [19] s.